Pengembangan Bahasa Anak Usia Dini: Studi Multi Situs di TK Mulia Desa Lampahungin dan TK Budi Bersama Desa Marindi - Nurita, Linda; Aslamiah, Aslamiah; Asniwati, Asniwati (JEA (Jurnal Edukasi AUD), 2024)
The disorder that most often affects children and is rarely recognized by parents is language development disorder. The research objective is to describe the language development model, the use of the environment as a learning resource and the involvement of parents or the community in early childhood language development. The research design used is a descriptive qualitative approach. Results of research regarding early childhood language development 1) The early childhood language development model used in Mulia Kindergarten in Lampahungin Village and Budi Bersama Kindergarten in Marindi Village is inviting children to talk (question and answer), tell stories, sing together, guess picture/media games and role playing, 2) Utilizing the environment as a learning resource in early childhood language development at Mulia Kindergarten, Lampahungin Village and Budi Bersama Kindergarten, Marindi Village, namely by utilizing educational game tools  in the form of storybooks and children's stationery in the classroom, as well as utilizing outdoor educational game tools in the form of swings. , slides, and seesaws, and 3) There are only 3 types of parental involvement in early childhood language development at Mulia Kindergarten in Lampahungin Village and Budi Bersama Kindergarten in Marindi Village, namely parenting, communication and learning with children at home.